Dinâmica da comunidade de Chironomidae (Diptera) em eventos de cheias e secas extremas em um rio Neotropica. - Favro, Alline (2021)
Climate change can make extreme drought and flood events more frequent, while damming large rivers can alter the hydrological regime by making droughts more prolonged and floods less intense. Together, both factors can affect aquatic communities. Here, the variation of Chironomidae community attributes between extreme floods and droughts in a neotropical floodplain river was investigated. The hypothesis that the abundance, richness, diversity and variability attributes of the Chironomidae community are reduced after extreme events was tested. Sampling took place quarterly from 2000 to 2012, although only a few years were selected to investigate our predictions. Twelve sampling periods were selected, which were divided into years in which, El Niño (extreme flood) and La Niña (extreme drought) phenomena occurred. In the Paraná River, three points were determined for the collection of benthic material, in transect: right bank, center and left bank of the river. We recorded 75 morphospecies of Chironomidae. The most common taxa in periods of extreme flooding were Djalmabatista sp 2, Lopescladius sp 1 and Tanytarsus type E. For periods of extreme drought, the most common taxa were Polypedilum (Tripodura) sp 4, Polypedilum sp 3 and Lopescladius sp 1. A composition and attributes of the Chironomidae community in the Paraná River varied between before and after extreme flood and drought events. Attributes such as Shannon-Wiener abundance, richness and diversity were reduced after extreme floods and, in contrast, tended to increase after extreme drought events (except Shannon diversity). Thus, it can be stated that the evaluated flood and drought events, despite being extreme, have different consequences in the Chironomidae community of the Paraná River. Given the environmental and global conditions we experience today, including climate change and dams, extreme events could be even more frequent in aquatic ecosystems. Therefore, it is essential to understand the consequences of extreme flood and drought events on ecosystems with high biodiversity and that provide relevant ecosystem services such as floodplain rivers.